2015
DOI: 10.1111/1744-7917.12178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three transgenic Bt rice lines for insecticidal protein expression and resistance against a target pest, Chilo suppressalis (Lepidoptera: Crambidae)

Abstract: Two transgenic rice lines (T2A-1 and T1C-19b) expressing cry2A and cry1C genes, respectively, were developed in China, targeting lepidopteran pests including Chilo suppressalis (Walker) (Lepidoptera: Crambidae). The seasonal expression of Cry proteins in different tissues of the rice lines and their resistance to C. suppressalis were assessed in comparison to a Bt rice line expressing a cry1Ab/Ac fusion gene, Huahui 1, which has been granted a biosafety certificate. In general, levels of Cry proteins were T2A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Our results indicated that the expression of exogenous Cry1Ab/c protein in transgenic HH1 varied temporally and spatially in rice grown on saline-alkaline and farmland soils. The aforementioned findings corroborate with those of other studies in which some insect-resistant Bt transgenic rice lines (Jiang et al, 2016; Wang et al, 2016; Zhang et al, 2016), cotton lines (Olsen et al, 2005; Siebert et al, 2009; Chen et al, 2012), and corn lines (Badea et al, 2010) presented temporal and spatial changes in the exogenous Bt protein expression level under natural insect pressure in field. In saline-alkaline soil, the average expression level of exogenous Cry1Ab/c protein in the leaves and stems of HH1 rice was significantly lower than that of plants grown on farmland soil throughout the growth stage.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that the expression of exogenous Cry1Ab/c protein in transgenic HH1 varied temporally and spatially in rice grown on saline-alkaline and farmland soils. The aforementioned findings corroborate with those of other studies in which some insect-resistant Bt transgenic rice lines (Jiang et al, 2016; Wang et al, 2016; Zhang et al, 2016), cotton lines (Olsen et al, 2005; Siebert et al, 2009; Chen et al, 2012), and corn lines (Badea et al, 2010) presented temporal and spatial changes in the exogenous Bt protein expression level under natural insect pressure in field. In saline-alkaline soil, the average expression level of exogenous Cry1Ab/c protein in the leaves and stems of HH1 rice was significantly lower than that of plants grown on farmland soil throughout the growth stage.…”
Section: Discussionsupporting
confidence: 91%
“…() predicted that rice yield has to be increased to 7850 kg/ha by 2030, resulting in a total of 200 million kg of rice per year to feed the Chinese people. Among multiple constraints to rice production, insect pests are an important factor (Wang et al ., ,b). In Chinese rice ecosystems, four major lepidopteran pests – rice striped stem borer Chilo suppressalis (Family Crambidae), yellow stem borer Scirpophaga incertulas (Family Pyralidae), pink stem borer Sesamia inferens (Family Noctuidae) and rice leaf roller Cnaphalocrocis medinalis (Family Pyralidae) – cause serious damage to rice, resulting in severe yield losses in every crop season (Chen et al ., ).…”
Section: Issues Facing Rice Production In Chinamentioning
confidence: 99%
“…In addition, some Bt rice lines have been stacked with other types of transgenes, such as the bar gene for herbicide tolerance (Yao et al ., ) and xa21 for disease resistance (Wang et al ., ). Most of the Bt rice lines have been shown to express high resistance to target pests in laboratory and field trials (Cohen et al ., ; Han et al ., ; Sui et al ., ; Tang et al ., ; Tu et al ., ; Wang et al ., ,b; Zhang et al ., ; Zheng et al ., ). In 2009, China's Ministry of Agriculture issued biosafety certificates for commercial production of the Huahui 1 and Bt Shanyou 63 Bt rice lines in Hubei Province, which raised expectation that China would use GM technology in commercial rice production (http://www.rsc.org/chemistryworld/China/Issues/2010/April-June/GMHotlyDebatedInChina.asp).…”
Section: Issues Facing Rice Production In Chinamentioning
confidence: 99%
“…Throughout the growing season, different Bt rice lines display different expression dynamics of Cry proteins. To sum up, expression dynamics can be classified into three patterns: (i) declining expression, with high expression at an early stage (seedling stage) with gradually decreased levels at later stages; this is the most frequent pattern not only in Bt rice, but also in Bt cotton, soybean and maize [22,25,26,34,38,56,62,68]; (ii) increasing expression, namely low expression at an early stage with increased expression levels at later stages [17,69]; and (iii) relatively consistent expression [26,34,70]. Interestingly, relatively high Cry protein expression levels were detected in lines expressing cry2Aa or cry9C genes among the Bt rice lines.…”
Section: Bt Ricementioning
confidence: 99%
“…For example, the corrected mortalities of 1st- to 6th-instar C. suppressalis in 7-day bioassays feeding on rice expressing cry1Ac + CpTI genes were 89.6%, 87.1%, 72.37%, 50.0%, 26.6%, and 0%, respectively [59]. Since the expression of Bt proteins in rice normally shows a declining tendency with the growth of rice plants, the resistance to target pests generally declined over the growth stages of rice plants; at mature stage most Bt rice lines showed relatively poor anti-pest efficacy [34,55,56,71]. However, Bt rice lines such as Bt -DL, mfb-MH86, and Huahui 1 showed high and consistent pest resistance throughout the growing season due to the stable expression of Bt protein in rice plants [22,26,34].…”
Section: Bt Ricementioning
confidence: 99%